Investigating key factors influencing decision-making in the design of buildings and places: a survey of stakeholders’ perception - Stanitsa, Avgousta; Hallett, Stephen H.; Jude, Simon (Springer, 2022)
Despite the impact of decision-making in the design of buildings and places, there is limited understanding concerning how decisions are best made, or how these should be evaluated and optimised. Additionally, technological advancements have increased human-to-machine interactions, altering existing decision-making processes. By understanding how novel technologies affect decisions, it motivates the development of the process, tools, and metrics. The aim of this paper is to investigate, quantify, and rank the relative importance of the decision-making factors contributing to the design of building and urban projects. A survey was conducted to gain an insight of stakeholders’ perceptions as to which are the influencing factors affecting decision-making processes in the design of buildings and places. Ten distinct factors were generated , of which, four were ranked as highly important for all stakeholder types, namely: Potential for Dynamic Operation, Thoroughness, Recency of Tools and Control. This study provides a new means to evaluate performance of decision-making processes, when these are undertaken, by developing and applying a quantitative data-driven, evidence-based methodological framework. The recipients of the findings will be the urban planners, designers, and academics who are interested in improving existing approaches in design and final decision outcomes utilising novel technologies.
Keywords: Decision-making; Perception; Data-driven innovation; Urban design